A Monte Carlo Model of Gas-Liquid-Hydrate Three-phase Coexistence Constrained by Pore Geometry in Marine Sediments - Chen, Jiangzhi; Rempel, Alan W.; Mei, Shenghua (Frontiers in Earth Science, 2021)
Gas hydrates form at relatively high pressures in near-surface, organic-rich marine sediments, with the base of the hydrate stability field and the onset of partial gas saturation determined by temperature increases with depth. Because of pore-scale curvature and wetting effects, the transition between gas hydrate and free gas occurrence need not take place at a distinct depth or temperature boundary, but instead can be characterized by a zone of finite thickness in which methane gas bubbles and hydrate crystals coexist with the same aqueous solution. Previous treatments have idealized pores as spheres or cylinders, but real pores between sediment grains have irregular, largely convex walls that enable the highly curved surfaces of gas bubbles and/or hydrate crystals within a given pore to change with varying conditions. In partially hydrate-saturated sediments, for example, the gas—liquid surface energy perturbs the onset of gas—liquid equilibrium by an amount proportional to bubble-surface curvature, causing a commensurate change to the equilibrium methane solubility in the liquid phase. This solubility is also constrained by the curvature of coexisting hydrate crystals and hence the volume occupied by the hydrate phase. As a result, the thickness of the three-phase zone depends not only on the pore space geometry, but also on the saturation levels of the hydrate and gaseous phases. We evaluate local geometrical constraints in a synthetic 3D packing of spherical particles resembling real granular sediments, relate the changes in the relative proportions of the phases to the three-phase equilibrium conditions, and demonstrate how the boundaries of the three-phase zone at the base of the hydrate stability field are displaced as a function of pore size, while varying with saturation level. The predicted thickness of the three-phase zone is inversely dependent on the grain size of the host sediment and increases dramatically when pores near complete saturation with hydrate and gas, requiring that interfacial curvatures become large.